Smoking behaviour in Germany: Evidence from the SOEP - Daniela Heilert; Ashok Kaul (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
As in most OECD countries, smoking prevalence and cigarette consumption have been decreasing in Germany since the early 2000s. This paper analyses whether smoking prevalence and cigarette consumption, as well as their development over time, differ between socio-economic subgroups. Identifying these differences provides insights into the effect of policy interventions on German smoking behaviour. Based on data from the Socio-Economic Panel (SOEP), a large longitudinal study of the German population, we find that both the decline in smoking prevalence and the decline in average cigarette consumption were probably driven by a behavioural change of younger people, as well as of those with a high educational level and those with a high income. People who quit smoking were on average more highly educated, had a higher income and had most likely a lower cigarette consumption (before quitting). In contrast, smoking prevalence increased among people who were older than 45 and had a low educational level and among those who were unemployed. Smoking prevalence among women was relatively constant over time. Indeed, the smoking prevalence of women and men converged over time, especially in older age groups. Daily cigarette consumption of smokers increased among 66-to-75-year-olds, although it decreased in all other age groups. One explanation might be that the tobacco control measures were successful only in certain socio-economic subgroups. Not only smoking prevalence, but also smoking intensity was higher among men, among those with a lower educational level and among those with a lower income. Especially for younger birth cohorts, smoking prevalence among those with a lower educational level was particularly high. Thus, based on data from 1998 through 2014, the so-called social gradient in smoking was only a distinct feature of younger birth cohorts, and not of older ones.
Keywords: I12; I18; 330; smoking prevalence; cigarette consumption; tobacco control measures; SOEP